2006
DOI: 10.1038/sj.onc.1209587
|View full text |Cite
|
Sign up to set email alerts
|

Re-expression of the tumor suppressor NF2/merlin inhibits invasiveness in mesothelioma cells and negatively regulates FAK

Abstract: The neurofibromatosis type 2 NF2 gene product, merlin, is a tumor suppressor frequently inactivated in malignant mesothelioma (MM). To investigate a possible correlation between merlin inactivation and MM invasiveness, we restored merlin expression in NF2-deficient MM cells. Re-expression of merlin markedly inhibited cell motility, spreading and invasiveness, properties connected with the malignant phenotype of MM cells. To test directly whether merlin inactivation promotes invasion in a nonmalignant system, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
117
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(129 citation statements)
references
References 52 publications
6
117
0
2
Order By: Relevance
“…In contrast, the phosphorylation of FAK on Y 397 , associated with kinase activation (Ruest et al, 2000) and increased cellular migration, was consistently elevated by 4-to 6-fold following HEI10 depletion ( Figure 4b). FAK is not only regulated by Merlin (Poulikakos et al, 2006), but also by association with focal-adhesion localized signaling proteins such as p130Cas (Brabek et al, 2005) and paxillin (Wade and Vande Pol, 2006). Total levels of paxillin and p130Cas were consistently elevated by 5-to 6-fold in HEI10-versus control-depleted cells (Figure 4c and d).…”
Section: Hei10 Is Required For Cell Proliferationmentioning
confidence: 75%
“…In contrast, the phosphorylation of FAK on Y 397 , associated with kinase activation (Ruest et al, 2000) and increased cellular migration, was consistently elevated by 4-to 6-fold following HEI10 depletion ( Figure 4b). FAK is not only regulated by Merlin (Poulikakos et al, 2006), but also by association with focal-adhesion localized signaling proteins such as p130Cas (Brabek et al, 2005) and paxillin (Wade and Vande Pol, 2006). Total levels of paxillin and p130Cas were consistently elevated by 5-to 6-fold in HEI10-versus control-depleted cells (Figure 4c and d).…”
Section: Hei10 Is Required For Cell Proliferationmentioning
confidence: 75%
“…A partial deficit in defasciculation of axon bundles by Schwann cells was observed in schwannomin mutants. Interestingly, it has been shown recently that focal adhesion kinase is involved in defasciculation (Grove et al, 2007), suggesting a possible link with schwannomin that is associated with focal adhesion kinase (FAK) and ␤1-integrins (Taylor et al, 2003) and can alter FAK activity (Poulikakos et al, 2006). Several other features suggested that Schwann cell membrane interactions were altered in schwannomin mutant mice.…”
Section: Discussionmentioning
confidence: 99%
“…On this basis, it has been argued that Merlin mediates both contact inhibition and tumour suppression by directly modulating mitogenic signal transduction at or near the plasma membrane [21,22]. Analysis of various cell types indicated that Merlin can potentially affect a variety of mitogenic pathways, such as Rac-PAK signalling [7,[23][24][25], activation of mTORC1 independently of Akt [26,27], the EGFR-Ras-ERK path- [26,27], the EGFR-Ras-ERK path-,27], the EGFR-Ras-ERK pathway, the PI3K-Akt pathway and FAK-Src signalling [28][29][30][31]. In addition, genetic studies in Drosophila and mice showed that Merlin contributes to the activation of the Hippo tumoursuppressor pathway [18,32,33].…”
Section: Introductionmentioning
confidence: 99%